TIKTOK AFFILIATE, A NEW MARKETING CHANNEL FOR BRANDS - Diana Novita; Agus Herwanto; Khasanah Khasanah (Jurnal Inovasi Penelitian, 2023)
TikTok, as one of the fastest growing social media, is now adding the TikTok Affiliate feature to it..Tiktok affiliate is one of the feature that tiktok shop offering to the people who wants to get the income through tiktok. In tiktok shop, we can choose wants to be a seller or to be an affiliate. If you choose to be affiliate, you must follow the term and condition that tiktok post. Affiliate marketing is basically a marketing strategy where brands will give certain commissions to those who promote and sell their products successfully. TikTok Affiliate, also known as Tiktok Shop Affiliate, is a sales method that allows creators to monetize their content. The trick is to promote a brand's product and then receive a commission on the sales generated. As a creator, you can promote products that are relevant to your audience, of course, with creative content ideas. So, apart from being a social media platform, Tiktok is now expanding its function to become a marketplace, where many users make buying and selling transactions for various products.